1997
DOI: 10.1080/07315724.1997.10718711
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge, attitude and practice among primary care physicians in Taiwan.

Abstract: This nationwide survey of nutrition-related knowledge and practices demonstrates the need for nutrition education for physicians. The questionnaire may be a useful instrument for future educational strategies in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 7 publications
7
28
5
Order By: Relevance
“…Consistent with prior studies [11,12,17], interns answered only 66% of knowledge questions correctly overall. They performed best on general nutrition knowledge and worse on specific nutrition interventions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with prior studies [11,12,17], interns answered only 66% of knowledge questions correctly overall. They performed best on general nutrition knowledge and worse on specific nutrition interventions.…”
Section: Discussionsupporting
confidence: 74%
“…Although prior studies have reported on the relationship between nutrition attitudes and knowledge [11][12][13], results have been equivocal and there are no studies examining the correlations among attitudes, self-perceived proficiency, and knowledge. This study seeks to further elucidate these relationships.…”
Section: Introductionmentioning
confidence: 86%
“…Attitudes towards and self-efficacy in nutrition care correlated positively with each other, but neither correlated with nutrition-related knowledge. Comparable to previous studies future doctors answered 64% of all the knowledge items [35,36,45]. An important finding of this study was that future doctors' nutrition-related knowledge was associated with their level of clinical training.…”
Section: Discussionsupporting
confidence: 56%
“…Previous findings have been equivocal in relating attitudes with knowledge and self-efficacy in nutrition [18,[35][36][37]. Even though one study has evaluated the association between attitudes, self-perceived proficiency and knowledge in a sample of internal medicine residents in the USA [35], no study have evaluated the relationship between knowledge, attitudes and self-efficacy in nutrition among undergraduate medical students.…”
Section: Introductionmentioning
confidence: 96%
“…The role of nutrition in health promotion, disease prevention and treatment of chronic diseases is well recognized (Hu et al, 1997;Schaller and James, 2005). Nutrition plays a critical role in numerous pathophysiological conditions, including such prevalent diseases as diabetes, cancer, and cardiovascular diseases (McGinnis and Foege, 1993).…”
Section: Cancer Preventionmentioning
confidence: 99%